Resistance of concrete to carbonation. Predicted and measured values in natural exposure - Ribeiro, M. S. (2009)
LNEC E 465 specification, in force by the Portuguese National Annex of EN 206-1, makes it possible to estimate the working life of the reinforced concrete structures by the application of models that make use of durability-related performance properties of concrete, such as, resistance to accelerated carbonation and chloride diffusion coefficient. In a study carried out in LNEC, several concrete mixes were produced with different w/c ratio and cement types, from which concrete specimens were prepared for characterization of relevant properties in laboratory, as well as for exposure in urbane and marine environments. This article presents and discusses the experimental results of carbonation up to 5 years of natural exposure, these results being compared with values estimated by the methodology established in LNEC E 465.